Characterization And Effect Of Sn(Iv) Chlorin E6 Dichloride Trisodium Salt In Photodynamic Therapy - Al-Khaza'leh, Khaled Abdu Bdaiwi (2009)
This study was performed to investigate the effect of pH and serum on Sn(IV) chlorin e6 dichloride trisodium salt photosensitizer and studying its effect in photodynamic therapy. Kajian ini dilakukan bagi menyelidik kesan pH dan serum ke atas foto pemeka garam Sn(IV) klorin e6 diklorid trinatrium dan mengkaji kesannya dalam terapi fotodinamik.